Salt finger convection at marginal stability - Rehman F.; Singh O.P. (My University, 2025)
Double diffusive salt fingers are alternating rising and falling convective structures that form due to density variation driven by varying diffusivity of the components. The degree of compensation between the component in terms of their effects on density stratification is measured by a dimensionless quantity, density ratio (Rρ). Salt fingers can form when density stability ratio Rρ lies in the range 1 < Rρ < τ−1, where τ is the diffusivity ratio. However, lately a new finger regime has been observed in the experiments of Hage and Tilgner [Phys. Fluids, 2010, 22, 076603–076607], where finger convection occurs even for Rρ < 1. It is observed in oceans that salt finger forms at low Rρ and distinctive finger formation occurs when Rρ → 1. However, critical information such as convective structures and fluxes are still unknown concerning what exactly happens at marginal stability (Rρ = 1). There has been a comprehensive study of salt finger convection at Rρ > 1 but scarcely any literature exists that has explored finger behaviour at Rρ = 1. In this paper we study the unexplored finger convection regimes numerically in a large range of governing parameter, for systems initially at Rρ = 1. © 2017 Informa UK Limited, trading as Taylor & Francis Group.